2005
DOI: 10.1128/iai.73.3.1553-1560.2005
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity to the Pathogenic Fungus Coccidioides posadasii Is Dependent on Toll-Like Receptor 2 and Dectin-1

Abstract: Coccidioides posadasii is a pathogenic fungus that causes endemic and epidemic coccidioidomycosis in the deserts of North, Central, and South America. How the innate immune system responds to the organism is not well understood. Here we show that elicited mouse peritoneal macrophages respond to spherules (the tissue form of the fungus) by producing proinflammatory cytokines as measured by quantitative PCR of cellular transcripts and by enzyme-linked immunosorbent assay (ELISA) assays for secreted protein. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
132
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 29 publications
5
132
0
4
Order By: Relevance
“…Results did not differ in experiments using bone marrow-derived macrophages (data not shown). The data emphasize the importance of dectin-1 in mediating inflammatory responses to inhaled fungal pathogens, because this receptor is now implicated in recognition of the filamentous fungus, A. fumigatus, as well as P. carinii and C. posadasii spherules (15,16,20,21). Inhalation of resting Aspergillus spores is common and constant, and a robust inflammatory response in the absence of a real threat could be disruptive to the airway.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Results did not differ in experiments using bone marrow-derived macrophages (data not shown). The data emphasize the importance of dectin-1 in mediating inflammatory responses to inhaled fungal pathogens, because this receptor is now implicated in recognition of the filamentous fungus, A. fumigatus, as well as P. carinii and C. posadasii spherules (15,16,20,21). Inhalation of resting Aspergillus spores is common and constant, and a robust inflammatory response in the absence of a real threat could be disruptive to the airway.…”
Section: Discussionmentioning
confidence: 79%
“…Dectin-1 mediates macrophage internalization of and activation by glucan-containing particles, including zymosan, C. albicans yeasts, Pneumocystis carinii, and Coccidioides posadasii spherules (15,16,20,21). We determined the role of dectin-1 in mediating murine macrophage responses to Aspergillus using laminarin (a soluble ␤-glucan) or anti-dectin-1 polyclonal Ab, which specifically blocks the receptor (13,14,16).…”
Section: Germ Tubes Activate Macrophages Through Dectin-1mentioning
confidence: 99%
“…Dectin-1 is a pattern-recognition receptor that has been implicated in defending against invasions by C. albicans (18)(19)(20), Aspergillus (21), Coccidioides (22), and Pneumocystis (23). This receptor is a single transmembrane protein with a carbohydrate recognition domain in its extracellular region that binds b-1,3-glucan (a major component of the cell wall of a variety of fungal pathogens), a transmembrane segment, and an N terminus cytosolic domain.…”
mentioning
confidence: 99%
“…Thus, Dectin-1 is thought to be the main β-glucan receptor involved in innate and adaptive immune responses to foreign antigens and pathogens, including β-glucan as an immune function stimulator. In addition, several reports revealed that Dectin-1 cooperates with pattern recognition receptors (PRRs) and Toll-like receptors (TLRs) in the innate immune responses to β-glucan recognition (13,43). These findings have prompted new interest in the interaction of β-glucan with its receptor (Dectin-1) or TLRs as co-receptors at the basic and clinical levels of medical research and immune therapeutics.…”
mentioning
confidence: 99%